Strategi Mafindo Tangani Hoaks Pilkada Jakarta 2024 Instagram Perspektif Dakwah Islam - Muhamad Taufik Fadhilah; Edi Amin (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. Mafindo, an independent community organization with the primary vision of creating a fact-friendly and hoax-free Indonesian social media ecosystem, faces the challenge of the massive spread of hoaxes ahead of the 2024 Jakarta gubernatorial election, particularly on Instagram. This study specifically aims to explain Mafindo's communication strategy in addressing these hoaxes and analyze their relevance to the perspective of Islamic da'wah in its educational approach during this crucial period. A qualitative case study method with a constructivist paradigm was applied, involving Mafindo's main subjects, Hafied Cangara's communication strategy theory, and Andi Faisal Bakti's Tabligh concept in Islamic communication theory. The study results reveal that Mafindo implemented a comprehensive strategy that included in-depth research by its internal research and development team, collaborative strategy development with national networks, partnerships with other organizations, direct hoax eradication, online and offline seminars, and periodic evaluation through volunteer discussions and routine reporting. This strategy proved quite successful, aligned with both theories, and effectively suppressed the spread of hoaxes while raising public awareness through education that integrated Islamic da'wah values. Abstrak. Mafindo, sebagai lembaga komunitas independen dengan visi utama menciptakan ekosistem media sosial Indonesia yang ramah fakta dan bebas hoaks, menghadapi tantangan penyebaran hoaks secara masif menjelang Pilkada Jakarta 2024 khususnya di platform Instagram. Penelitian ini secara khusus bertujuan untuk menjelaskan strategi komunikasi Mafindo dalam menangani hoaks tersebut serta menganalisis relevansinya dengan perspektif dakwah Islam dalam pendekatan edukasinya selama periode krusial itu. Metode studi kasus kualitatif dengan paradigma konstruksivisme diterapkan, melibatkan subjek utama Mafindo, teori strategi komunikasi dari Hafied Cangara, serta konsep Tabligh dalam teori komunikasi Islam menurut Andi Faisal Bakti. Hasil penelitian mengungkap bahwa Mafindo menerapkan strategi komprehensif yang mencakup riset mendalam oleh tim litbang internal, penyusunan strategi secara kolaboratif bersama jaringan nasional, kemitraan dengan organisasi lain, pemberantasan hoaks secara langsung, penyelenggaraan seminar daring maupun luring, serta evaluasi berkala melalui diskusi relawan dan pelaporan rutin. Strategi ini terbukti cukup berhasil, selaras dengan kedua teori tersebut, serta efektif menekan penyebaran hoaks sambil meningkatkan kesadaran masyarakat melalui edukasi yang mengintegrasikan nilai-nilai dakwah Islam.